Role of the kinetochore/cell cycle checkpoint protein ZW10 in interphase cytoplasmic dynein function - Varma, Dileep (The Rockefeller University Press, 2006)
Zeste white 10 (ZW10) is a mitotic checkpoint protein and the anchor for cytoplasmic dynein at mitotic kinetochores, though it is expressed throughout the cell cycle. We find that ZW10 localizes to pericentriolar membranous structures during interphase and cosediments with Golgi membranes. Dominant-negative ZW10, anti-ZW10 antibody, and ZW10 RNA interference (RNAi) caused Golgi dispersal. ZW10 RNAi also dispersed endosomes and lysosomes. Live imaging of Golgi, endosomal, and lysosomal markers after reduced ZW10 expression showed a specific decrease in the frequency of minus end–directed movements. Golgi membrane–associated dynein was markedly decreased, suggesting a role for ZW10 in dynein cargo binding during interphase. We also find ZW10 enriched at the leading edge of migrating fibroblasts, suggesting that ZW10 serves as a general regulator of dynein function throughout the cell cycle.